De novo centromere formation in pericentromeric region of rice chromosome 8. (29th June 2022) - Xue, Chao; Liu, Guanqing; Sun, Shang; Liu, Xiaoyu; Guo, Rui; Cheng, Zhukuan; Yu, Hengxiu; Gu, Minghong; Liu, Kai; Zhou, Yong; Zhang, Tao; Gong, Zhiyun
SUMMARY: Neocentromeres develop when kinetochores assemble de novo at DNA loci that are not previously associated with CenH3 nucleosomes, and can rescue rearranged chromosomes that have lost a functional centromere. The molecular mechanisms associated with neocentromere formation in plants have been elusive. Here, we developed a Xian ( indica ) rice line with poor growth performance in the field due to approximately 272 kb deletion that spans centromeric DNA sequences, including the centromeric satellite repeat CentO, in the centromere of chromosome 8 ( Cen8 ). The CENH3‐binding domains were expanded downstream of the original CentO position in Cen8, which revealed a de novo centromere formation in rice. The neocentromere formation avoids chromosomal regions containing functional genes. Meanwhile, canonical histone H3 was replaced by CENH3 in the regions with low CENH3 levels, and the CenH3 nucleosomes in these regions became more periodic. In addition, we identified active genes in the deleted centromeric region, which are essential for chloroplast growth and development. In summary, our results provide valuable insights into neocentromere formation and show that functional genes exist in the centromeric regions of plant chromosomes. Significance Statement: The mechanisms underlying neocentromere formation in plants have been elusive. In this study, we demonstrate that CentO deletion led to the expansion of the CENH3‐binding domain and neocentromere formation in rice. Our findings also provide valuable insights into neocentromere formation and show that functional genes exist in the centromeric regions of plant chromosomes.